2018
DOI: 10.1017/s0305000918000429
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of English possessives by a bilingual child: Do input and usage frequency matter?

Abstract: Previous research in child language shows that many aspects of language acquisition are frequency-linked. This study tests whether input or usage frequency predicts the order of acquisition and accuracy of a bilingual Greek–English child's English possessives. The child was followed longitudinally from age 2;6 to 3;11. Order of acquisition was comparable to that of same-aged monolingual children. The child's usage frequency and order of acquisition were highly correlated with input frequency, while her accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In fact, the weight of evidence to date suggests that adult bilinguals can show positive transfer even when word order varies across languages (Hatzidaki et al, 2011;Hwang et al, 2018). One case study of a bilingual child also suggested that positive transfer could occur, despite a lack of similarities in the constructions in the two languages (Babatsouli and Nicoladis, 2019). If positive transfer can occur even in the absence of similar word orders, then the form of abstract representation might be primarily in terms of function.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the weight of evidence to date suggests that adult bilinguals can show positive transfer even when word order varies across languages (Hatzidaki et al, 2011;Hwang et al, 2018). One case study of a bilingual child also suggested that positive transfer could occur, despite a lack of similarities in the constructions in the two languages (Babatsouli and Nicoladis, 2019). If positive transfer can occur even in the absence of similar word orders, then the form of abstract representation might be primarily in terms of function.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the literature would benefit from longitudinal work assessing the impact of accented input on bilingual children's language development. The longitudinal case study by Babatsouli and Nicoladis (2019) is a positive indication that children can learn from non-native input over time. We also show that children do indeed learn from non-native input as confirmed by their within average range language scores.…”
Section: The Effect Of Accented Language Input On Children's Language...mentioning
confidence: 99%
“…These findings were also verified by Kaltsa et al (2020), who compared Albanian-Greek to English-Greek bilinguals on gender attribution with overall lower performance in gender agreement, especially in the case of pseudo-words and better performance in gender attribution to masculine and neuter nouns than to feminine ones. Additionally, Babatsouli and Nicoladis (2019), in a longitudinal study, examined the acquisition of English possessives by a bilingual Greek-English-speaking child and found that the acquisition of possessives in the dominant language, i.e., Greek, facilitates the acquisition of possessives (that encompass gender) in the weaker language, i.e., English. Recently, Alexiadou et al (2021) tested gender agreement in adolescent heritage speakers of Greek whose other language is English and reported that most gender mismatches are identified in noun phrase internal agreement contexts and verified that neuter is used as the learner default for L2 Greek.…”
Section: Monolingual and Bilingual Greek Speakers And The Acquisition...mentioning
confidence: 99%